Pharmacological Evaluation, Anti-Oxidant And Hepatoprotective Activity Of Tradescantia Fluminensis Leaves Extract On Experimental Rats - Ali, Shadab; Dhakad, Kehar singh; Kumar Singhai, Akhilesh (Journal of Neonatal Surgery, 2025)
The present study investigates the pharmacological, antioxidant, and hepatoprotective activities of Tradescantia fluminensis leaves extract in experimental rats. The plant material was collected, authenticated, dried, and extracted using the Soxhlet extraction method, followed by percentage yield determination. A phytochemical screening confirmed the presence of flavonoids, phenolics, alkaloids, tannins, terpenoids, and saponins, which are known for their medicinal properties. The antioxidant activity was assessed using the DPPH radical scavenging assay, which demonstrated a strong free radical neutralization capacity, indicating its potential in oxidative stress management. The FTIR study identified key functional groups contributing to its biological activity. The acute oral toxicity study revealed that the extract is safe at therapeutic doses. For the hepatoprotective study, hepatotoxicity was induced in rats using Paracetamol, and the protective effects of T. fluminensis extract were evaluated through biochemical parameters including ALP, SGOT, SGPT, and total bilirubin levels. The treatment significantly improved these markers, suggesting its hepatoprotective potential. Histopathological analysis further confirmed reduced hepatic inflammation and cellular damage in extract-treated groups compared to control groups. The study demonstrates that T. fluminensis possesses potent antioxidant and hepatoprotective properties, which can be attributed to its bioactive constituents. The findings suggest its potential use as a natural therapeutic agent for oxidative stress-induced liver diseases, though further clinical research is needed for validation.